2018
DOI: 10.1371/journal.pone.0200707
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic changes by benznidazole in a specific treatment for Chagas disease

Abstract: Chagas disease (Cd) is the third most common parasitic disease that causes damage to human health. Even a century after its description by Carlos Chagas and advances in its control, it remains a neglected disease. To eradicate the parasite or reduce the parasitic load, specific treatment for Trypanosoma cruzi (T. cruzi) is advisable; benznidazole (BNZ) is the drug that is currently prescribed. The purpose of this study is to report the adverse events (AE) due to the use of BNZ as a specific treatment for Cd, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The elevated ALT values decreased for most animals during the recovery phases of the study (Supplemental Table 4). Similar ALT changes have been noted in humans treated with 5-10 mg/kg/day [23]. No other serum chemistry abnormalities and no hematological changes were consistently identified in the treated macaques (Supplemental Tables 4, 5).…”
Section: Resultssupporting
confidence: 76%
“…The elevated ALT values decreased for most animals during the recovery phases of the study (Supplemental Table 4). Similar ALT changes have been noted in humans treated with 5-10 mg/kg/day [23]. No other serum chemistry abnormalities and no hematological changes were consistently identified in the treated macaques (Supplemental Tables 4, 5).…”
Section: Resultssupporting
confidence: 76%
“…Symptoms of BZN-induced liver toxicity may include fatigue, abdominal pain, jaundice, and elevated liver enzymes in the blood [ 20 ]. Specifically, BNZ treatment results in elevations of AST, ALT, and ALP [ 38 ]. Our group has shown that a vaccine-linked chemotherapy strategy allows the reduction of BNZ dose, while still effectively reducing cardiac inflammation and fibrosis, and improving cardiac function [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of BZN-induced liver toxicity may include fatigue, abdominal pain, jaundice, and elevated liver enzymes in the blood (20). Specifically, BNZ treatment results in elevations of AST, ALT, and ALP (38). Our group has shown that a vaccine-linked chemotherapy strategy allows the reduction of BNZ dose, while still effectively reducing cardiac inflammation and fibrosis, and improving cardiac function (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%